Determinants of the Underpricing Rate of Stocks: Study on Companies Conducting IPO on the IDX - Rudianto, Dudi; Ratnawati, Aryanti; Susanto, Bambang; Susilo, Tri Pujadi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This article analyzes the determinants that affect the level of underpricing in property and real estate sub-sector companies that conduct Initial Public Offerings (IPOs) on the Indonesia Stock Exchange for the 2015-2019 period. The variables used in this study include financial factors consisting of Current Ratio (CR) for liquidity ratios, Debt to Equity Ratio (DER) for leverage ratios, Return On Assets (ROA) for profitability ratios, and Earning Per Share (EPS) for ratios. market, as well as non-financial factors consisting of Underwriter Reputation (UR) and Share Offering Percentage (SOP). The results show that simultaneously all financial and non-financial factors have a significant effect on the level of underpricing, with a very strong influence. While partially CR, ROA, UR and SOP are factors that have a significant influence on the level of underpricing. So it can be concluded that financial and non-financial factors have the same influence on the level of underpricing.